Study of glycemic status, thyroid function and vitamin D3 level in children with β thalassemia major in a tertiary care center - Kumar Solanki, Dhiraj; Dewangan, Shashikant; Sahu, Bhoopendra (Pediatric Review: International Journal of Pediatric Research, 2020)
Introduction: β thalassemia has emerged as a huge public health problem worldwide. Thyroxine reserve is reduced in multitransfused thalassemia patientsanddiabetes can also be a considerable complication.Vitamin D3 deficiency is noted in thalassemia patients and is related to bone diseases. Aims and Objectives: Study of glycemicstatus, thyroid function, and vitamin D3 level in children with βthalassemia major. Method:Socio-demographic information wascollected by using the pretested and predesigned structured pro forma by interview technique. HbA1c level, vitamin D3 level,and thyroid function had been obtained from the lab. Result:In 89% of subjects TSH levels were normal with a mean value of 5.04.In 10.9%it was increased witha mean value of TSH being 6.67.VitaminD3 level in 2% children was below 20ng/ml, 50.50% had between 21 to 29ng/ml and 47.52% had between 30-60 ng/ml. Vitamin D3 deficiency increased with a higher blood transfusion rate (p-value 0.000). In 88.12%of the study, subjectsHbA1c was normal, 11.18%were inthe pre-diabetic range,and none of the subjects were diabetic as per HbA1C results. The mean value of HbA1C in normal children was 4.79%whereas in prediabetic children mean value of HbA1C was 6.13%. Conclusion: In the present study multiple endocrine abnormalities were common in multi transfused thalassemia major patients. Prevalence of subclinical hypothyroidism and prediabetes increased with a higher blood transfusion rate and higher serum ferritin level. Prevalence of subclinical hypothyroidism and prediabetes increased with age (p-value <0.05).